A Facile and Fast One Flask Synthesis of Unsaturated Azlactones by Microwave Activation - K. Tripathy, Pradeep (Asian Journal of Chemistry, 2016)
2-Substituted-2-oxazolin-5-ones (2), generated by cyclizing a-N-acylaminoacids (1) with ethylchloroformate in the presence of triethylamine in benzene, affords 2-substituted-4-arylmethylene-2-oxazolin-5-ones (3), on reaction with aromatic aldehydes by microwave irradiation. All the steps are carried out in one flask.